2018
DOI: 10.1128/jcm.01917-17
|View full text |Cite
|
Sign up to set email alerts
|

Point-Counterpoint: Piperacillin-Tazobactam Should Be Used To Treat Infections with Extended-Spectrum-Beta-Lactamase-Positive Organisms

Abstract: INTRODUCTIONBeta-lactam/beta-lactamase inhibitor combination antimicrobials (BLBLIs) are among the most controversial classes of antibiotic agents available for the treatment of infections caused by extended-spectrum-beta-lactamase (ESBL)-producing Gram-negative bacteria (ESBL-GNR). Piperacillin-tazobactam (PTZ) is one of the most frequently utilized antibiotic agents for empirical Gram-negative bacterial coverage and remains active against a large proportion of ESBL-GNR strains. Furthermore, good antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 26 publications
0
15
1
2
Order By: Relevance
“…According to a study piperacillin-tazobactam can be used alternatively in some infections but not widely recommended. 13,14 A study reported ESBL maximum resistance against ampicillin (100%) followed by cephalosporins as 94.12% resistant against cefuroxime, 61.76% resistant for ceftriaxone. 15…”
Section: Resultsmentioning
confidence: 99%
“…According to a study piperacillin-tazobactam can be used alternatively in some infections but not widely recommended. 13,14 A study reported ESBL maximum resistance against ampicillin (100%) followed by cephalosporins as 94.12% resistant against cefuroxime, 61.76% resistant for ceftriaxone. 15…”
Section: Resultsmentioning
confidence: 99%
“…Second, although we conducted propensity score matching and multivariate analysis to adjust for selection bias and potential confounders, adverse effects from non-matched confounding factors could remain. Third, caution should be exercised when generalising the results of this study to other ESBL-producing Enterobacteriaceae infections, because most patients in our cohort had BSI due to E. coli , which is usually related to better outcomes than other Enterobacteriaceae [ 15 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of PTZ therapy against certain MRE strains (i.e., those producing ESBL) differs significantly depending on the study. Thus, its utility to treat infections by these pathogens remains controversial (20). Indeed, in the only randomized clinical trial performed, PTZ was shown to be less effective than meropenem in the treatment of bloodstream infections produced by Enterobacteriaceae ESBL-producer strains (21).…”
Section: Discussionmentioning
confidence: 99%